Estimating the Welfare Costs of Reforming the Iraq Public Distribution System : A Mixed Demand Approach - Krishnan, Nandini; Ramadan, Racha; Olivieri, Sergio (World Bank, Washington, DC, 2017)
The Iraqi Public Distribution System is the largest universal, in-kind subsidy system in the world. In 2012, the Public Distribution System transfers accounted for as much as 30 percent of incomes of the poorest 10 percent of the Iraqi population and provided 70 percent of the calories of the poorest 40 percent. In effect, the Public Distribution System remains the only safety net program that covers all the poor and vulnerable in the country. Yet, it is a very inefficient and expensive means to deliver transfers to the poor and creates distortions in the economy as well as an unsustainable fiscal burden. The fiscal crisis since mid-2014 has put reform of the Public Distribution System back on the agenda. This paper employs a mixed demand approach to analyze the consumption patterns of Iraqi households and quantify the welfare impact of a potential reform of the Public Distribution System in urban areas. The results show that household consumption of Public Distribution System items is relatively inelastic to changes in price. Consumption is more inelastic for the poorest quintiles and, for much of the population, these goods are not inferior, but rather normal goods. Cross-sectional comparisons suggest that with improvements in welfare levels, and with well-functioning markets, some segments of the population are substituting away from the Public Distribution System and increasing their consumption of market substitutes. The removal of all subsidies will require compensating poor households by 74.4 percent of their expenditures compared with nearly 40 percent for the richest households in urban areas.